Avocado Seed Extracts (Parsea americana Mill.) Bioactive Compounds Profile as a Source of Antioxidants - Jubaidah, Siti (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Antioxidants are compounds that may neutralize free radicals and highly reactive molecules that might damage cells, thereby protecting the body from numerous ailments. A recent study found that high dosages of synthetic antioxidants increased the risk of cancer. This made researchers start to develop natural ingredients that can be used as natural antioxidants. One of the natural antioxidants that can be used is the avocado plant.Many phytochemicals, including phenolics, flavonoids, tannins, saponins, oxalates, phytic acids, and alkaloids, are present in seed wastes. Avocado seeds have been studied primarily as antioxidants in 70% and 100% ethanol solvents using the FRAP and DPPH methods. There is no detailed information on the above test using 96% ethanol with various antioxidant testing methods such as the ABTS method (2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid), which has been linked to active phenolic compounds, flavonoids, and proanthocyanidins as a high natural antioxidant chemical compound.According to research findings, the avocado seed extract in 95% ethanol contains secondary metabolites such as alkaloids, flavonoids, saponins, tannins, and steroids. It has 62.18%GAE±0.73 phenolics, 0.157%QE±0.01 flavonoids and 2.1841 mg/L±0.25 proanthocyanidins. With IC50 of 0.6419 mg/L±0.04 ascorbic acid and 3.2467 mg/L±0.27 and a sample. This antioxidant activity has a very strong category. Keyword : Antioxidants, Avocados, ABTS, Phenolics, Flavonoids, Proanthocyanidins